(untitled) (Damascus University Journal for legal sciences, 2024)
It increased with the emergence of the financial deficit in many countries. The search for many ways to confront the fiscal deficit in the public budget. The method of participation between the public and private sectors is on of the alternative mothed to confront of the financial deficit, especially after the failure of the measures taken by countries, including (Increasing domestic revenues - Improving tax collection procedures - Combating tax evasion - Accelerating the completion of tax accumulation - Increasing investment revenues - Control and rationalization of public spending) Because such measures taken by countries in order to reduce the deficit, especially on the revenue side seem largely outside the control of the financial authorities Whether due to political conditions or global economic conditions, and currently the Corona pandemic. The state’s resort to concluding such contracts is a new methodology in order to reduce the financial burdens borne by its budget, as the participatory method allows the establishment of economic projects without the use of public resources. Funding from the private sector generally allows the transfer of financial, industrial and other risks to the project company.